Audit of Renal Function Monitoring and Indications in Patients Prescribed Memantine at Ribchester Centre: A Review of Compliance With Pre-Prescription Guidelines - Laiba Khalid; Akash Kumar (BJPsych Open, 2025)
Aims: To assess whether renal function tests are appropriately reviewed prior to the prescription of memantine, in accordance with NICE clinical guidelines, ensuring the safety and effectiveness of medication.